PURIFICATION OF RECOMBINANT HSP70 BY IMMOBILIZED METAL AFFINITY CHROMATOGRAPHY (IMAC) AND ITS ROLE IN IMMUNE ENHANCEMENT AND ANTIOXIDANT ENZYME PROTECTION - Rihab H. Zghair,; G.M. Aziz,; A.H. Ad’hiah, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
By utilizing Ni-NTA affinity chromatography, the expressed recombinant HSP70 protein was purified, and the SDS-PAGE analysis was used to assess its purity. Purified recombinant HSP70 was used to immunize BALB/c mice, and this had a considerable impact on the anti-HSP70 antibody titers. The results of this study show that the adjuvanted hsp70 injected into the mice had a good immunogenic property. In this study, we measured the effects of HSP70 on catalase stability after exposure it to different range of temperature (40, 45, 50, 55, 60) ˚C, and found that the catalase kept its remaining activity% (99% and 17%) when incubating it in 40 and 60ºC respectively in the present of HSP70, compared to its remaining activity % without HSP70 which were 95%, 10% respectively.  Also noticing that the enzyme kept 90% of its remaining activity % when incubating it with buffer at pH 8.0 and 95% of it at pH 6.0 comparing with its remaining activities % (81%, 90%) respectively without HSP70. while the activity was completely eliminated in pH 2.0. Also studied the inhibition effect of some heavy-metals with different concentrations (10, 20,30mg/L) on catalase activity with and without HSP70.